2021
DOI: 10.3390/molecules26164889
|View full text |Cite
|
Sign up to set email alerts
|

Yield, Characterization, and Possible Exploitation of Cannabis Sativa L. Roots Grown under Aeroponics Cultivation

Abstract: Cannabis sativa L. has been used for a long time to obtain food, fiber, and as a medicinal and psychoactive plant. Today, the nutraceutical potential of C. sativa is being increasingly reappraised; however, C. sativa roots remain poorly studied, despite citations in the scientific literature. In this direction, we identified and quantified the presence of valuable bioactives (namely, β-sitosterol, stigmasterol, campesterol, friedelin, and epi-friedelanol) in the root extracts of C. sativa, a finding which migh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 54 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…[23] The absorption band at 1054 cm À 1 is characteristic of CÀ O stretching vibration of equatorial hydroxy groups of sterols. [27] In 2021, Ferrini et al [28] identified that the main compounds in C. sativa roots are phytosterols (βsitosterol, campesterol and stigmasterol) and triterpenoids (friedelan-3-one and epifriedelanol). Interestingly, although the C. Sativa roots from this work were collected in a different location (northeastern Brazil), the same major compounds were observed.…”
Section: Resultsmentioning
confidence: 99%
“…[23] The absorption band at 1054 cm À 1 is characteristic of CÀ O stretching vibration of equatorial hydroxy groups of sterols. [27] In 2021, Ferrini et al [28] identified that the main compounds in C. sativa roots are phytosterols (βsitosterol, campesterol and stigmasterol) and triterpenoids (friedelan-3-one and epifriedelanol). Interestingly, although the C. Sativa roots from this work were collected in a different location (northeastern Brazil), the same major compounds were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Ferrini et al [19] grown Cannabis sativa var. Kompolti under aeroponic system and found that the roots of aeropoically grown plants showed a 64-fold and 13-fold higher fresh (FW) and dry weight (DW) as compared to soil grown plants, respectively; the aerial parts showed a 39-fold and 44-fold higher FW and DW; the stems' average diameter and the mean leaves area increased by 3.89-fold and 8.9-fold, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…grown in an aeroponic system had higher yields compared to the same plants grown in soil (Movahedi and Rostami 2020). This system was efficient for the production of bioactive molecules from roots of medicinal crops, such as chlorogenic acid in A. lappa and β-sitosterol in Cannabis sativa (Hayden 2006;Ferrini et al 2021). For various medicinal plants, root apices constitute the main sites where active substances are produced and stored (Watson et al 2015).…”
Section: Aeroponicsmentioning
confidence: 99%